1924
DOI: 10.1037/h0073513
|View full text |Cite
|
Sign up to set email alerts
|

The Feeling Value of Lines.

Abstract: Among the factors that determine the affective value of any visual presentation (such as color, subject, balance, light and shade), line forms have occupied an important position in the opinions of writers on Aesthetics. Cox 1 says • Straight lines will always express rigidity and stiffness while curves will express some sort of growth or motion The vertical line is a line of stability, of strength and vigor .... All these characteristics of lines may be the result of association or they may have some deeper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
96
1
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 0 publications
7
96
1
1
Order By: Relevance
“…4). These results are consistent with evidence from previous studies establishing a preference for curved objects ranging from simple lines to furniture and car interiors (12)(13)(14)(15)(16)(17)(18)(19)(20) and the grounding of that preference in affect (16,18), and extend them to the domain of architecture. Neuroanatomically, our results demonstrated that judging the beauty of curvilinear spaces was associated exclusively with an increase in ACC activity over and above judging the beauty of rectilinear spaces (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…4). These results are consistent with evidence from previous studies establishing a preference for curved objects ranging from simple lines to furniture and car interiors (12)(13)(14)(15)(16)(17)(18)(19)(20) and the grounding of that preference in affect (16,18), and extend them to the domain of architecture. Neuroanatomically, our results demonstrated that judging the beauty of curvilinear spaces was associated exclusively with an increase in ACC activity over and above judging the beauty of rectilinear spaces (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the selection of contour was empirically motivated because a number of previous studies have demonstrated that it affects aesthetic judgments. Specifically, early psychological investigations going back almost 100 y examined the effect of contour on feelings (12)(13)(14). In the spirit of early empiricists, experimenters manipulated contour using simple stimuli, such as lines or abstract displays composed of curves or angles.…”
mentioning
confidence: 99%
“…However, we also showed strong effects of pulse size, with larger pulses conveying lower valence and higher arousal. Unlike previous research [3,18,29] contour did not influence valence ratings, possibly because the differences between our contours were less obvious than others [29].…”
Section: Discussioncontrasting
confidence: 46%
“…Arousal decreased and pleasure increased as greyscale colours changed from black through grey to white. Research has also identified hedonic perceptions of shape and contour, finding that people have a consistent preference for curved over pointed objects [3,18], possibly due to the inherent "threat" conveyed by sharp objects [4].…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation